Predicting autologous hamstring graft diameter and finding reliable measurement levels in the Zhuang population using preoperative ultrasonography - Huang, Xiao-Li; Zheng, Hong-Yu; Shi, Ze-Feng; Yang, Hui-Hui; Zhang, Bing; Yang, Xiao-Chun; Wang, Hong; Tan, Ru-Xin (Frontiers in Physiology, 2022)
Purpose: To evaluate the feasibility of using ultrasonography to preoperatively predict the autologous hamstring graft diameter for anterior cruciate ligament (ACL) reconstruction in the Zhuang population and determine a reliable measurement level using ultrasound. Methods: Twenty-four Zhuang patients who were scheduled for ACL reconstruction using four-strand semitendinosus tendon (ST) and gracilis tendon (G) (4S-STG) autografts were included in this study. Ultrasonographic examinations of the ST and the G on the damaged side were conducted before the operation. We recorded the transverse diameter (TD), anterior–posterior diameter (APD), cross-sectional area (CSA), and perimeter (P) of the tendons. The measurements were obtained from two levels of the tendons: the widest point of the medial femoral epicondyle (level 1) and the myotendinous junction of the sartorius (level 2). We also calculated the combined (ST + G) TD, APD, CSA, and p values. Then, we obtained the intraoperative measurements. The correlation between the ultrasonic and intraoperative measurements was analyzed, and the advantages of the ultrasonic measurements at the two different levels were compared. Results: When we measured at level 1, we found that part of the ultrasonic measurements were correlated with intraoperative measurements. The preoperative CSA of the G (P-GCSA) can be used to distinguish a 4S-STG autograft diameter of ≥8 mm (p < 0.01, mean difference = 3.7). The area under the P-GCSA curve was 0.801 (p < 0.05). A P-GCSA of 8.5 mm2 could be used to predict a 4S-STG autograft diameter of ≥8 mm with a sensitivity of 61.1% and specificity of 83.3%. However, there was no correlation between the ultrasonic and intraoperative measurements at level 2. Conclusion: Preoperative ultrasound can be used to predict the sufficient diameter of 4S-STG autografts when considering patients from Zhuang who are undergoing ACL reconstruction. The ultrasonic measurement should be obtained at the widest point of the medial femoral epicondyle.